Prevalensi Kelainan Refraksi Myopia Akibat Pembelajaran E-Learning pada Siswa SMK Negeri 1 Purwokerto - Laila Anggraeni; Wahjoe Handini; Raden Risang Haryo Chandra Dewantoro (EMVIRO Jurnal Ilmiah Penelitian Kesehatan, 2024)
The prevalence of myopia has significantly increased over the past 50–60 years and is no longer limited to urban areas in East Asia. In the United States, approximately 148 million people (51% of the population) use visual correction aids, with 34 million wearing contact lenses. The incidence of myopia rises with age: 3% among children aged 5–7 years, 8% in those aged 8–10 years, 14% in ages 11–12 years, and up to 25% among adolescents aged 12–17 years. This study aims to determine the prevalence of refractive error (myopia) due to e-learning among students at SMK Negeri 1 Purwokerto. A quantitative survey method with a cross-sectional approach was used, involving questionnaires and direct visual acuity examinations. The study involved 26 respondents, with the majority being female (88.46%). The results showed that 4 students (15.38%) were diagnosed with refractive error (myopia) after engaging in e-learning. The number of students with visual acuity decline increased from 6 students (23.08%) to 10 students (38.46%) after the implementation of online learning. These findings suggest that e-learning, particularly with excessive gadget use, contributes to the rising incidence of myopia among students. This study highlights the potential link between prolonged screen time and visual health, underlining the need for preventative measures to reduce the adverse effects of digital learning on eye health.